A study of Conceptual Metaphors Used in English and Vietnamese Cosmetic Advertisements” - Lê Thị Thùy Dương (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The aim of this study is to examine the conceptual metaphors used in English and Vietnamese cosmetic advertisements. It also discovers some similaritie and differences in using conceptual metaphors used in English and Vietnamese cosmetic advertisements. Moreover, this study will be useful for those concerning about conceptual metaphors in advertisin